Genetic Variation in the IL-6 and HLA-DQB1 Genes Is Associated with Spontaneous Clearance of Hepatitis C Virus Infection - Waldron, Paul Ravi (J Immunol Res, 2016)
Background. Millions of people are infected with hepatitis C virus (HCV) worldwide and 30% spontaneously clear the infection. Reasons for HCV clearance without antiviral treatment are not well understood. Methods. Blood was collected for DNA analysis from patients with chronic HCV infection or evidence of spontaneous clearance. To overcome anticipated limitations of small sample size, primary analyses consisted of a candidate gene analysis of 12 preselected genes based on known association with host immunologic response to HCV infection. To further reduce the impact of multiple testing on power, a single likelihood ratio test was conducted for each gene using all associated SNPs assayed on the Illumina Quad 610/660W chip. Step-down permutation methods were used to adjust for multiple testing in all analyses. Results. Ninety-five and 62 patients with HCV chronic infection or spontaneous clearance, respectively, were included for analysis. HLA-DQB1 (p = 1.76⁎10(−5)) and IL-6 (p = 0.0007) genes were significantly associated with spontaneous HCV clearance. IL-28B was not significantly associated with spontaneous clearance (p = 0.17). Conclusion. Our whole-gene analytic strategy identified a previously unreported association of IL-6 with spontaneous clearance of HCV infection. We also confirmed the finding that HLA-DQB1 is associated with spontaneous resolution of HCV infection.